Intensity and Profitability of Smallholder Cassava Farmers’ Participation in Value Addition in Afijio Local Government Area of Oyo State, Nigeria - Oluwatayo, Isaac; Idiaye, Chuks; Yusuff, Mutiat (Applied Studies in Agribusiness and Commerce, 2022)
This study investigated the intensity and profitability of smallholder cassava farmers’ involvement in cassava value addition in Afijio Local Government Area of Oyo State, Nigeria. Data were collected from 150 cassava farming households through the use of a well-structured questionnaire and employing a simple random sampling procedure. The data collected included information on the socioeconomic characteristics of the respondents, intensity of value addition among the respondents, factors influencing their decisions to add value as well as the extent of value addition, profitability of cassava value addition and the factors that determined the profitability level of the enterprises. The data were analyzed using the descriptive statistics for profiling the socioeconomic characteristics of the respondents, gross margin was used to measure profitability, and ordinary least squares regression model was used to determine the factors influencing the decisions of smallholder cassava farmers to add value to cassava as well as the extent of value addition among them. The results revealed that majority of the respondents were females (52.7%) with average age between 31-40 years of age while the average household size (52.7%) is between 6-10 members. Regression analysis of the determinants of the intensity of value addition revealed that the decisions to add value to cassava as well as the extent to which value was added were influenced positively by educational attainment, household size, and years of experience in cassava value addition. Results of the gross margin analysis revealed a positive return on variable costs thus indicating that the cassava value adding enterprise is a profitable one. These findings presented the need for all the stakeholders concerned to focus their attentions on proffering solutions to the challenges faced by cassava processors within the minimum time possible.JEL code: L11, M11, M21, Q13, R32